Outcome of Carotid Endarterectomy in a Tertiary Center of Nepal: A Retrospective Study - Kadel, Prashiddha B; Shrestha, Uttam K; Shrestha, Kajan R; Gurung, Dinesh (Journal of Institute of Medicine Nepal, 2021)
Introduction Carotid endarterectomy for carotid artery disease is one of the surgeries performed by vascular surgeons for carotid artery disease. The objective of this study is to describe the early and late outcome of the patient undergoing carotid endarterectomy and the association between the complication and comorbidities present previously in the patient. Methods All patients undergoing carotid endarterectomy at Manmohan Cardiothoracic Vascular and Transplant Centre between April 2010 to April 2020 were included. The follow-up data for upto a year from medical and clinical records, telephone interview regarding the immediate and late postoperative complications in patients with and without comorbidities were investigated and compared. Results The total study population was 42 patients. Two patients (4.7%) developed stroke, one immediately in postoperative period and the other during follow up. There were two deaths (4.7%) postoperatively due to cardiac events and three (7.14%) recurrences of carotid stenosis among whom one (2.5%) developed late stroke. Twenty six patients (61.90%) were symptomatic prior to the procedure of which 20 patients (47.61%) had brain infarct. Overall one year survival was 95.2% post procedure and overall complication rate was 7.14%. The consequence in the form of death and stroke occurred more in the patients with comorbidities (3vs1) p=0.42. Conclusion The immediate and late postoperative complications following carotid endarterectomy were death (4.7%), stroke (4.7%), cranial nerve injury (9.5%). The most frequent cause of death was postoperative cardiac event. Though major complications occurred more frequently in patients having comorbidities, it was statistically insignificant.